Static and dynamic magnetic response of fragmented haldane-like spin chains in layered Li3Cu2SbO6 - Koo, Changhyun; Klingeler, Rüdiger (Journal of the Physical Society of Japan, 2016)
The structure and the magnetic properties of layered Li3Cu2SbO6 are investigated by powder X-ray diffraction, static susceptibility, and electron spin resonance studies up to 330 GHz. The XRD data experimentally verify the space group C2/m with halved unit cell volume in contrast to previously reported C2/c. In addition, the data show significant Li/Cu-intersite exchange. Static magnetic susceptibility and ESR measurements show two magnetic contributions, i.e., quasi-free spins at low-temperature and a spin-gapped magnetic subsystem, with about half of the spins being associated to each subsystem. The data suggest ferromagnetic-antiferromagnetic alternating chains with JFM = −285 K and JAFM = 160 K with a significant amount of Li-defects in the chains. The results are discussed in the scenario of fragmented 1D S = 1 AFM chains with a rather high defect concentration of about 17% and associated S = 1/2 edge states of the resulting finite Haldane chains.